Professional Quality of Life, Job Satisfaction, and Intention to Leave among Psychiatric Nurses: A Cross-Sectional Study - Shaher Hamaideh; Abdallah Abu Khait; Hanan Al-Modallal; Rami Masa'deh; Ayman Hamdan-Mansour; Mohammed AlBashtawy (MDPI AG, 2024)
Psychiatric nurses are challenged with high levels of stress, which, in turn, lower their professional quality of life (ProQoL) and job satisfaction and increase their intention to leave jobs in psychiatric settings. An adequate level of ProQoL improves patient care provision. The purpose of this study is to assess the levels, relationships, and predictors of the professional quality of life of Jordanian psychiatric nurses and their job satisfaction and intention to leave their job. A descriptive cross-sectional design was used to collect data using the Professional Quality of Life Scale-5 from a convenience sample. Data were collected from 144 psychiatric nurses working in the largest psychiatric hospitals run by Ministry of Health, military, and university-affiliated hospitals. The results showed that the mean scores for compassion satisfaction (CS), burnout (BO), and secondary traumatic stress (STS) were 35.21, 27.0, and 26.36, respectively. The mean scores for intention to leave and job satisfaction were 2.33 and 3.7, respectively. The income level, educational level, intention to leave, and job satisfaction significantly differed in the CS dimension. Nurses' age, intention to leave, and job satisfaction significantly differed in BO. Nurses' age, years of experience, frequent C-shifts worked, and work affiliation were different in STS. Burnout, STS, and educational level predicted CS. CS, STS, job satisfaction, and level of education predicted BO. BO, CS, and frequently working night C-shifts predicted STS. Due to the presence of nurses reporting low levels of ProQoL, job satisfaction, and intension to leave, more studies are needed to assess the factors that affect ProQoL among psychiatric nurses and to evaluate interventional programs that improve the quality of life of psychiatric nurses. This is important in retaining nurses and increasing their job satisfaction. There is a need for interventions that enhance ProQoL. Also, longitudinal studies that measure ProQoL overtime are recommended. This study was not registered.